Contrastive Analysis of Tabe Politeness Speech Acts in Bugis and Sumimasen in Japanese (Pragmatic Study) - Putri Bintang Pratiwi Harahap; Kartyka Nababan (Journal of Japanese Language Education and Linguistics, 2024)
This research investigates the level of politeness exhibited by Tabe in Bugis and Sumimasen in Japanese. The researchers do a contrastive analysis to examine the differences and similarities between Tabe in Bugis and Sumimasen in Japanese, which encompasses the act of begging and the pragmatic aspect of politeness. This research uses a contrastive descriptive qualitative methodology, in which the data consists of elaborate qualitative information rather than numerical values. This data is examined by using two distinct approaches, specifically descriptive and contrastive data analysis. The findings of this investigation in the term "tabe" holds significant symbolism in Bugis language and culture, serving as a means to kindly and respectfully request permission. By strategic use of "tabe" in appropriate circumstances, individuals can demonstrate profound gratitude and courtesy towards others, enhance social connections, and uphold societal harmony. Likewise, the use of "sumimasen" in Japan underscores cultural principles that emphasize courtesy, modesty, and social concord. The word is employed in several contexts to apologise, request assistance, or convey appreciation, and serves to sustain positive relationships and prevent conflict in daily contacts.